Polyamine metabolism links gut microbiota and testicular dysfunction - Qi Zhao (BMC, 2021)
Abstract Background Male fertility impaired by exogenous toxins is a serious worldwide issue threatening the health of the new-born and causing infertility. However, the metabolic connection between toxic exposures and testicular dysfunction remains unclear. Results In the present study, the metabolic disorder of testicular dysfunction was investigated using triptolide-induced testicular injury in mice. We found that triptolide induced spermine deficiency resulting from disruption of polyamine biosynthesis and uptake in testis, and perturbation of the gut microbiota. Supplementation with exogenous spermine reversed triptolide-induced testicular dysfunction through increasing the expression of genes related to early and late spermatogenic events, as well as increasing the reduced number of offspring. Loss of gut microbiota by antibiotic treatment resulted in depletion of spermine levels in the intestine and potentiation of testicular injury. Testicular dysfunction in triptolide-treated mice was reversed by gut microbial transplantation from untreated mice and supplementation with polyamine-producing Parabacteroides distasonis. The protective effect of spermine during testicular injury was largely dependent on upregulation of heat shock protein 70s (HSP70s) both in vivo and in vitro. Conclusions The present study linked alterations in the gut microbiota to testicular dysfunction through disruption of polyamine metabolism. The diversity and dynamics of the gut microbiota may be considered as a therapeutic option to prevent male infertility. Video Abstract